2019
DOI: 10.1111/nph.15825
|View full text |Cite
|
Sign up to set email alerts
|

Functional trait evolution in Sphagnum peat mosses and its relationship to niche construction

Abstract: Summary Species in the genus Sphagnum create, maintain, and dominate boreal peatlands through ‘extended phenotypes’ that allow these organisms to engineer peatland ecosystems and thereby impact global biogeochemical cycles. One such phenotype is the production of peat, or incompletely decomposed biomass, that accumulates when rates of growth exceed decomposition. Interspecific variation in peat production is thought to be responsible for the establishment and maintenance of ecological gradients such as the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 75 publications
(102 reference statements)
1
17
1
Order By: Relevance
“…The second criterion that could be employed to help deciding whether clade or subclade models should be applied is based on niche overlap analyses and niche similarity tests (Broennimann et al., 2012; Warren et al., 2008), which failed here to demonstrate niche divergence. Instead, evidence for niche conservatism was found in half of the species considered, in line with broad support for this mechanism (Peterson et al., 1999) and emerging evidence for it in bryophytes (Johnson et al., 2015; Piatkowski & Shaw, 2019). In bryophytes, evidence for niche expansion outside of the native range in invasive species is lacking (Mateo et al., 2015), but correlations between genetic and ecological distances, potentially pointing to ecological specialization, have been recurrently reported (Hutsemékers et al., 2010; Magdy et al., 2016; Mikulášková et al., 2015; Pisa et al., 2013; Szövényi et al, 2009).…”
Section: Discussionmentioning
confidence: 52%
“…The second criterion that could be employed to help deciding whether clade or subclade models should be applied is based on niche overlap analyses and niche similarity tests (Broennimann et al., 2012; Warren et al., 2008), which failed here to demonstrate niche divergence. Instead, evidence for niche conservatism was found in half of the species considered, in line with broad support for this mechanism (Peterson et al., 1999) and emerging evidence for it in bryophytes (Johnson et al., 2015; Piatkowski & Shaw, 2019). In bryophytes, evidence for niche expansion outside of the native range in invasive species is lacking (Mateo et al., 2015), but correlations between genetic and ecological distances, potentially pointing to ecological specialization, have been recurrently reported (Hutsemékers et al., 2010; Magdy et al., 2016; Mikulášková et al., 2015; Pisa et al., 2013; Szövényi et al, 2009).…”
Section: Discussionmentioning
confidence: 52%
“…Our inability to detect a correlation between subgenus and biomass gain may reflect the situation in the field. Piatkowski & Shaw (2019) did not detect an influence of phylogeny on the majority of traits in their study on 15 Sphagnum species and suggested that the environmental context can obscure the phylogenetic signal. Our novel method creates an artificial but standardized environment for 19 Sphagnum species.…”
Section: Resultsmentioning
confidence: 90%
“…Then, phylogenetic inference was performed using NGphylogeny.fr (Lemoine et al., 2019). The resulting Sphagnum phylogenetic tree was supported by the high‐resolution tree recently built for Sphagnum mosses and based on 16 loci (Piatkowski & Shaw, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…When the species are missing from the mega‐tree, V.Phylomaker uses species that are sister to or closely related with some species or genera in the mega‐tree to accurately attached species to their relatives in the phylogenetic tree. As bryophytes are missing from V.Phylomaker, we used gene sequence from the ribosomal non‐coding protein trnL intron and trnL‐F intergenic spacers to build Sphagnum phylogeny (Piatkowski & Shaw, 2019). We selected these loci as they were the only available sequences for all Sphagnum species in our species list in the GeneBank database.…”
Section: Methodsmentioning
confidence: 99%